Membaca Tanpa Memahami: Tantangan Keterampilan Membaca Pemahaman Di Sekolah Dasar - Ayu Siti Juariah (International Forum of Researchers and Lecturers, 2024)
The learning outcomes of Indonesian in understanding reading texts at the elementary school (SD) level are still low. This study aims to explore the challenges of reading comprehension skills in elementary school students, where many students are able to read technically but have difficulty understanding the reading content. This study examines the phenomenon of the gap between technical reading ability and reading content comprehension in elementary school students in Indonesia. Although students are able to read texts fluently, they often have difficulty understanding the meaning and context of more complex readings. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews, reading and text comprehension tests, and documentation at SD Negeri Bunter II, Cimanggung District, Sumedang Regency. The results show that this problem is caused by several factors, such as teaching methods that are less interactive and focus on reading techniques without providing comprehension strategies, lack of use of technology in learning, and low motivation of students to read more complex texts. The text comprehension test showed that only 35% of students were able to understand the content of the reading well. These findings emphasize the need to use more varied, creative, and technology-based learning methods to improve students' reading comprehension. This study provides important recommendations for teachers and schools in implementing a more effective approach to improve students' literacy skills